Động lực tự điều chỉnh trong cải thiện kĩ năng nói tiếng Anh của sinh viên ngành Giáo dục mầm non - Đặng Út, Phượng; Trần Thị Kim Liên, Trần Thị Kim Liên (Tạp chí Giáo dục, 2026)
Currently, with the demand for English at all educational levels, students majoring in Early Childhood Education not only need basic English communication skills but also the ability to access international early childhood education materials, use songs, games, storytelling, simple instructions, and interact appropriately with children in English. This cross-sectional descriptive-correlational study examined self-reported motivational regulation strategies for improving English speaking among 473 Early Childhood Education students from two Vietnamese universities. A 24-item Vietnamese adaptation of the Self-Regulated Motivation for Improving Speaking English as a Foreign Language scale was organized a priori into four theory-based dimensions: task value activation, regulation of the learning environment, regulation of affect, and regulation of the classroom environment. Internal consistency was high (α = .908-.931; total α = .967), although the factor structure was not revalidated in this sample; therefore, dimension-level results are interpreted descriptively. The overall mean was 3.525 (SD = .645). Task value activation had the highest descriptive mean (M = 3.706), whereas regulation of the learning environment had the lowest (M = 3.418). Correlations among dimensions ranged from .637 to .820, indicating substantial overlap that may partly reflect common-method variance. English language enjoyment showed the strongest bivariate association with the overall score, although the relationship remained weak. (rho = .244, p < .001). The findings reflect self-reports rather than speaking proficiency or causal policy effects.